Re-estimating Effective Equilibrium Exchange Rates in the West African Economic and Monetary Union: New Evidences and Perspectives - Adom, Assandé Désiré (Eastern Journal of Economics and Finance, 2015)
This study assesses the long-run dynamics of nominal effective rates in the UEMOA through the post-devaluation era, 1995-2010. The study used two distinct approaches the behavioral equilibrium exchange rate (BEER) and the permanent equilibrium exchange rate (PEER) - to estimate the long-run values for the nominal effective exchange rate (NEER) in each country. Overall, the results indicate that the NEERs of all countries in the union are misaligned with respect to their sustainable levels. It also suggests the need for a revaluation of the CFAF. These findings are innovative in the literature, for they contrast with the conclusions of many past studies and public discourses in the political arena. Furthermore, it is found that misalignments in most countries have accelerated in the post-devaluation era, which may cast doubts about the effectiveness of this policy-action. On the other hand, this research work sends a signal to current decision-makers inviting them to make the appropriate exchange rate corrections in an attempt to reinforce the long-term viability of the CFAF and ensure a balanced economic growth across the union.